Impact of body-mass-index (BMI) on effective dose of whole-body [18F] fluorodeoxyglucose PET/CT examinations - Lukuman, Bashiru; Murat, Husain; Said, Mohamad Aminuddin; Yaakob, Yazid; Ibahim, Mohamad Johari; Tahir, Dahlang; Karim, Muhammad Khalis Abdul (Elsevier, 2026)
This study evaluates the influence of body-mass index (BMI) on radiation dosimetry in PET/CT procedures, focusing on radiation dose variations across BMI categories. Data were collected from 1000 patients at Institut Kanser Negara, Malaysia, comprising 516 females (51.6 %) and 484 males (48.4 %) who underwent whole body 18F-FDG PET/CT procedures from July 2023 to December 2023. Parameters such as administered dose, CTDIvol, DLP, and effective dose were analysed. The findings indicate that CTDIvol and DLP values increase with BMI, imposing higher radiation doses for larger patients to maintain diagnostic image quality. Administered doses showed minimal variability across different BMI categories and genders, reflecting standardized radiotracer administration protocols. Male patients generally received higher radiation doses than female patients due to differences in body composition and size. Effective dose (ECT) from CT scans was significantly higher in patients with higher BMI, ranging from 7.1 ± 2.4 mSv for underweight to 19.3 ± 4.7 mSv for obese patients. Effective dose (EPET) from PET scans remained relatively consistent across BMI categories, ranging from 0.2 ± 0.07 mSv for underweight to 0.2 ± 0.07 mSv for obese patients, highlighting the need for personalized dosing techniques. All pairwise differences were statistically significant at p > 0.001. This study underscores the necessity for personalized dosimetry protocols that account for BMI variations to optimize imaging quality while minimizing radiation exposure. The study recommends developing and implementing such protocols and establishing guidelines for radiopharmaceutical dosage adjustments based on BMI categories to ensure standardized and safe practices across clinical settings.